Solar home with energy management by frugal discharge - mothayakul, tararat; Sripadungtham, Patamaporn; Boonbumroong, Usa (Interdisciplinary Research Review, 2018)
This paper presents Energy Management for a Solar Home at the Rural Electrification Learning Center, King Mongkut’s University of Technology Thonburi (Bangkuntien). The solar home comprises of power sources from a solar system, a battery system, and a transmission line system. Electricity rate is different depending on the energy source and electricity consumption period. The solar home system equipment are connected on SMA Sunny Home Manager to collect and display data via a website. Data analyses of solar home from July to December 2015 were divided into 2 cases; a home without solar system and the solar home with energy management by Frugal discharge. It was found that, a solar home with energy management by Frugal discharge can save the electricity bill by 24,820 baht per year. If the electricity is sold back to a transmission line system, a solar home with energy management by Frugal discharge can increase revenues by 12,497 baht per year. On economic analysis at interest rate of 10% per year, a solar home with energy management by Frugal discharge has a payback period of 16 years, the NPV value is negative, the B/C Ratio lower than 1 and the IRR of 2.96%.